2023
DOI: 10.24171/j.phrp.2022.0287
|View full text |Cite
|
Sign up to set email alerts
|

Association between face covering policies and the incidence of coronavirus disease 2019 in European countries

Abstract: Objectives: This study was conducted to determine the impact of the strengthening or relaxation of face covering mandates on the subsequent national case incidence of coronavirus disease 2019 (COVID-19) in Europe as the full vaccination rate was increasing.Methods: European countries in which case incidence increased for 3 consecutive weeks were monitored and analyzed using COVID-19 incidence data shared by the World Health Organization (WHO). The epidemic trend of COVID-19 in Europe was compared with that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These studies encompass research samples from over 88% of countries and regions worldwide, with each study focusing on a different geographical scope. Table 1 provides a breakdown of the studies: eight evaluated the effectiveness of NPIs in containing the COVID-19 pandemic on a global scale [20][21][22][23][24][25][26][27], three focused on Europe [28][29][30], two on the United States [31,32], one on Asia [10], and one each on India [33], France [11] and Korea [34]. In terms of quality assessment, the seventeen studies received a moderately high score, averaging 13…”
Section: Summary Of Literature Screening and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies encompass research samples from over 88% of countries and regions worldwide, with each study focusing on a different geographical scope. Table 1 provides a breakdown of the studies: eight evaluated the effectiveness of NPIs in containing the COVID-19 pandemic on a global scale [20][21][22][23][24][25][26][27], three focused on Europe [28][29][30], two on the United States [31,32], one on Asia [10], and one each on India [33], France [11] and Korea [34]. In terms of quality assessment, the seventeen studies received a moderately high score, averaging 13…”
Section: Summary Of Literature Screening and Backgroundmentioning
confidence: 99%
“…Facial coverings are a form of personal protective equipment used to shield the face from various external hazards like splashes, droplets, and aerosols. Among the summarized evidence, only one study (Sookhyun Kim et al) [29] found that the incidence of COVID-19 was significantly higher after the relaxation of face covering mandates. Other studies found no association between the implementation of facial covering policies and a reduction in COVID-19 cases [10,20,23,31,32].…”
Section: Summary Of the Main Findingsmentioning
confidence: 99%